Study of the thermal behavior in solid state of Mn(II)-diclofenac complex - Kobelnik, Marcelo; Quarcioni, Valdecir Ângelo; de Almeida, Adélia Emília [UNESP]; Ribeiro, Clóvis Augusto [UNESP]; Crespi, Marisa Spirandeli [UNESP] (Ecletica Quimica, 2018)
The preparation, characterization and thermal behavio of Mn(II)-diclofenac solid-state complex was investigated b simultaneous TG/DTA and DTG curves, DSC, X-ray powde diffraction (XRD) and scanning electron microscopy (SEM techniques. The thermal evaluation was carried out with sample masse of 2 and 5 mg, with the purpose of comparing the values of activatio energy regarding dehydration, monotropic phase transition and therma decomposition in both samples mass. The DSC curves were obtained i opened and with crimped lids crucibles of aluminum under oxyge purge gas and static air (without purge gas). The DTA and DSC curve show an exothermic peak between 150-180 °C depending on heatin rate, which can be attributed to the monotropic non-reversible reaction The activation energy (Ea/kJ mol-1) to dehydration, the monotropi phase transition and the first thermal decomposition step wer determined by Capela-Ribeiro nonlinear isoconversional method. Th activation energy under oxygen dynamic purge gas shows lower value compared to those obtained under static air.
Keywords: Activation energy; Mn(II)-diclofenac complex; Monotropic reaction; Thermal analysis